A Practical Review of Green Supply Chain Management: Disciplines and Best Practices. Issue 2 (31st August 2016) - Pourhejazy, Pourya; Kwon, Oh Kyoung
Abstract : Nowadays, climate change and environmental pollution have become major international concerns, in which logistics and manufacturing activities are playing the major role. In the past decade, more attention has been directed toward environmental issues than ever before. The Paris agreement is one of the most recent milestones in this regard. Due to local and international legislation, managers are highly encouraged to seek out sustainable innovations and strategies to reduce the negative impacts of their business activities. An array of academic and practical activities has been formed around the greening of the supply chain (SC). This paper attempts to review and classify green supply chain management (GSCM) disciplines and best practices from a practical point of view. The authors also investigate the different areas of application and review the GSCM practices in some well-known companies. On this basis, the paper disclose the superiority of Apple company over the other studied cases in applying green practices, particularly in the manufacturing and design areas, while the parcel delivery company has been quite active in the green transportation and green marketing. It is also shown that all of the reviewed cases have been successful in implementing green logistics initiatives thus far.